2020
DOI: 10.1111/jocs.15090
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of biventricular repair for shone's complex

Abstract: Background: Shone's complex is a rare lesion affecting the mitral valve (MV) and left ventricular outflow tract (LVOT). The objective of this study is to report the outcomes after Shone's complex repair, the growth of mitral and aortic valve and LVOT, and long-term survival. Methods: This retrospective study included all patients diagnosed with Shone's complex, who underwent biventricular repair. Data including patients' characteristics, type of the MV lesion and the associated lesions were collected. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
10
3
Order By: Relevance
“…The most common cause of MVR was congenital mitral valve disease, followed by Shone's complex. The etiological diagnosis may affect the outcomes after MVR 18 ; however, we did not observe any effect in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…The most common cause of MVR was congenital mitral valve disease, followed by Shone's complex. The etiological diagnosis may affect the outcomes after MVR 18 ; however, we did not observe any effect in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…Elmahrouk et al reported that preoperative AV size was a risk factor for reoperation, but they did not show a correlation between LVOT stenosis and reoperation. 5 In the presented study, there was no correlation between LVOT stenosis and reoperation. In this series, six of nine reoperation patients underwent septal myectomy, modified Konno or Ross-Konno procedure.…”
Section: Reoperationscontrasting
confidence: 47%
“…series, 17 out of 37 patients underwent MV surgery and concomitant LVOT surgery. 5 Perrier et al 2 reported a rate of 55% for their patients with a history of LVOT intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Shone complex, or Shone syndrome, is characterized by the simultaneous presence of supravalvular mitral membrane, parachute mitral valve, muscular or membranous subvalvular aortic stenosis, and coarctation of aorta [14]. This peculiar syndrome leads to a progressive lack of hemodynamic stability; in fact, a simple disequilibrium of the pressure gradient, as commonly observable in a normal subject from clinostatism to orthostatism, could represent a serious condition capable of inducing a systemic loss of perfusion.…”
Section: Patient No 3: 17-year-old Patient With Shone Complexmentioning
confidence: 99%